Whisper: A High Capacity File Encrypting and Hiding Method in an Audio File - Aldarwbi, Mohammed; Al-Kharobi, Talal (Discoveries in Agriculture and Food Sciences, 2017)
The advance of internet and multimedia allows for tremendous transferring of digital media data and the percentage of time that users spend in online activity and exchanging important information is increasing day by day. Besides that, the simplicity in editing and transmitting the files, makes them vulnerable for stealing or disrupting. Therefore, it is of utmost importance to find an effective way for sending the sensitive information without being noticed by the eavesdroppers or hackers. Cryptography and Steganography are considered the main protection techniques used against eavesdroppers or hackers. Securing the transmission of the sensitive information over the internet and the publicly available media is essential. Intercepting the transmitted information over internet in any form - text, data, voice, image or video should be denied or at least made it harder by encrypting them or hiding them within any cover media. The need for an innovative approach to secure the personal information is increasing dramatically especially by the organizations and governments as they exchange a highly sensitive information. œIn this work, beside using the most common used encryption methods for encrypting the hidden file and the key, a novel idea for hiding the required information